2019
DOI: 10.1016/j.healthplace.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use in the sexual borderlands: The smoking contexts and practices of bisexual young adults

Abstract: Little is known about why bisexual people use tobacco at higher rates than any other sexual identity group. Non-binary sexualities, such as bisexuality, exist within the socially constructed borderland between homosexuality and heterosexuality. Exploration of the everyday smoking contexts and practices of bisexual individuals may reveal unique mechanisms driving tobacco use. We employed a novel mixed method, integrating real-time, smartphone-administered surveys of (non)smoking situations, location tracking, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…Previous research has shown that pod mod products tend to be favored by youth because they can be easily concealed and used discretely (Fadus et al, 2019), whereas normative influence in sexual minority social networks may instead encourage use of products that are more socially visible. For instance, a study of lesbian, gay, bisexual, and transgender youth identified tobacco use as a mechanism to signal social belonging and conform to normative pressure (Remafedi, 2007), and a study of bisexual young adults reported tobacco use facilitated social interactions with peers and romantic or sexual interests (McQuoid et al, 2019). Thus, more socially visible products may be used by sexual minority adolescents in efforts, conscious or unconscious, to signal belonging and facilitate relationship building and development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that pod mod products tend to be favored by youth because they can be easily concealed and used discretely (Fadus et al, 2019), whereas normative influence in sexual minority social networks may instead encourage use of products that are more socially visible. For instance, a study of lesbian, gay, bisexual, and transgender youth identified tobacco use as a mechanism to signal social belonging and conform to normative pressure (Remafedi, 2007), and a study of bisexual young adults reported tobacco use facilitated social interactions with peers and romantic or sexual interests (McQuoid et al, 2019). Thus, more socially visible products may be used by sexual minority adolescents in efforts, conscious or unconscious, to signal belonging and facilitate relationship building and development.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies which reported mean age and dichotomous male–female gender distribution of the sample, participants tended to be younger (mean 30.9, SD 8.0 years, based on 21 studies) and mostly women (mean 68.7% of the sample, based on 19 studies). The topics of study were smoking [ 16 , 17 ], alcohol consumption [ 18 - 22 ], mental health [ 23 - 29 ], dietary behavior [ 30 - 35 ], drug use [ 36 , 37 ], physical activity [ 38 ], and tinnitus management [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concordant with recommendations regarding exploratory analyses (Rothman, 1990), we did not use a false discovery rate or adjustment for multiple comparisons as we are interested in identifying potential areas for further research. We present ORs for the overall sample as well as stratified by SGM group classification and age (Matthews, Blosnich, Farmer, & Adams, 2014; McQuoid, Thrul, Ozer, Ramo, & Ling, 2019). For the purposes of the stratified analyses, we classified individuals as either cisgender lesbian, cisgender gay, cisgender bisexual, or transgender/nonbinary; for the age analyses, we classified people as either young adult (18-24 years old) or older adult (25+ years old).…”
Section: Methodsmentioning
confidence: 99%